2019
DOI: 10.31234/osf.io/x2fuq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association between meaning in life and harmful drinking is mediated by individual differences in self-control and alcohol value

Abstract: Manuscript accepted for publication in Addictive Behaviors Reports, 25th January 2020.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 30 publications
2
7
1
Order By: Relevance
“…It was recently found that the presence of MiL as measured with the MLQ is associated with less harmful drinking (Copeland et al 2020). Interestingly, the search for meaning showed an inverse relation (more harmful drinking).…”
Section: Meaning In Lifementioning
confidence: 99%
“…It was recently found that the presence of MiL as measured with the MLQ is associated with less harmful drinking (Copeland et al 2020). Interestingly, the search for meaning showed an inverse relation (more harmful drinking).…”
Section: Meaning In Lifementioning
confidence: 99%
“…a life characterized by comprehension and significance; George and Park 2013) is often divided into two subscales (Steger et al 2006): 'presence' reflects the extent to which a person currently experiences life meaning and 'search' reflects the extent to which a person is actively seeking life meaning. Research reliably demonstrates that presence of meaning in life is inversely associated with alcohol consumption (Robinson et al 2007;Schnetzer et al 2013;Krentzman et al 2017;Copeland et al 2020;Csabonyi and Phillips 2020), however the relationship between search for meaning in life and alcohol consumption is less clear: one study found a positive association (Copeland et al 2020) whilst another study found no significant association (Csabonyi and Phillips 2020) between the two. Put another way, some evidence shows that elevated search for meaning in life is characterized by higher levels of alcohol consumption, which may in part be due to frustration or disappointment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One recent cross-sectional study found that people with high presence of meaning have lowered behavioral economic demand for alcohol and lower scores on the alcohol use disorders identification test (AUDIT; Copeland et al 2020), which may in part be due to elevated alcohol-free alternative reinforcement. Different factors may contribute to increasing alcohol-free reinforcement, one of them being age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations